(untitled) (Journal of Bio-Science, 2011)
Context: Bottom condition and aquatic plants of the water bodies play important roles on the population growth of Macrobrachium lamarrei. Objective: To study the effects of different bottoms and aquatic vegetations on the population growth of Macrobrachium lamarei. Materials and Methods: Brood stocks of M. lamarrei were maintained in mini ponds, and they were fed in 24h with supplemental diets. For observing the effect of bottom condition on the prawn population three tanks (each 32"x36"x21"with a constant water depth of 16") were prepared: tank I, cemented bottom with no vegetation; tank II, muddy bottom and with water hyacinth and tank III, sandy-muddy bottom (2:1) with water hyacinth. To study the effect of aquatic plants on the population separate four tanks were prepared with sandy-muddy bottom (1:1) and subsequently with different vegetations. These were: tank I with Ipomea, tank II with Alternanthera, tank III with Eichornia, Ipomea, Alternanthera, Wolffia and Lemna, tank IV with Wolffia and Lemna. M. lamarrei of both sexes (N = 40-55) were released in each tank depending on the experimental type. Number of prawns of different stages was counted after 3 and 6 months to determine the effect of bottom condition, and after 3, 6 9 and 12 months to record the effect of aquatic plants. Results: M. lamarrei was found to prefer sandy-muddy bottom than cemented or muddy bottoms. The total population was recorded after six months as 760 (tank I), 1018 (tank II) and 1542 (tank III) where the initial number of released prawns was 55. Aquatic vegetations affected the population growthdifferently. After 12 months the total population was recorded as 2590 (tank I), 3416 (tank II), 1360 (tank III) and 1580 (tank IV). Population of M. lamarrei was maximum when Alternanthera (Santi sak) was present. Conclusion: The results provide baseline information for establishing culture system for M. lamarrei and related smaller species of this genus simultaneously. Keywords: Bottom condition; aquatic vegetation; population; Macrobrachium lamarrei. DOI: http://dx.doi.org/10.3329/jbs.v18i0.8777 JBS 2010; 18(0): 60-65